Solubility and ordering of Ti, Ta, Mo and W on the Al sublattice in L12-Co3Al. (September 2015) - Koßmann, J.; Hammerschmidt, T.; Maisel, S.; Müller, S.; Drautz, R.
Abstract: Co–Al–W-based alloys are promising new materials for high-temperature applications. They owe their high-temperature strength to hardening by ternary L12 -Co3 (Al1−x W x ) precipitates, which may form even though binary Co3 Al is not stable. In the current work, density functional theory calculations are performed to study the solubility and ordering of the transition metals W, Mo, Ti, and Ta at the Al sublattice in L12 -Co3 Al. The sublattice disorder is modelled with a newly parametrised cluster expansion and compared to results using special quasi-random structures. Our results for W and Mo show that the mixing energy exhibits a minimum at approximately x = 0.7. However, the computed small values of the mixing energies indicate that W and Mo atoms are fully disordered with the Al atoms already at low temperatures. For Ti and Ta we find no sizeable driving force for ordering with the Al atoms. The computed solubilities on the Al sublattice obtained are in the range of 40–80 meV/atom for W and Mo and less than 25 meV/atom for Ti and Ta. Graphical abstract: Highlights: We investigate the sublattice solubility of W, Mo, Ti, and Ta in L12 -Co3 Al. We use density functional theory calculations to fit cluster expansions (CE). Our results are compared to special quasi-random structures (SQS) calculations. DFT solubilities on the Al lattice are (meV): ∼55 (W & Mo), 15 (Ti), and <10 (Ta). For all 4 elements total sublattice disorder is expected.